2008
DOI: 10.1007/s10856-008-3413-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polydimethylsiloxane (PDMS) induced proliferation and neural-like cells differentiation of umbilical cord blood-derived mesenchymal stem cells

Abstract: Stem cell-based therapy has recently emerged for use in novel therapeutics for incurable diseases. For successful recovery from neurologic diseases, the most pivotal factor is differentiation and directed neuronal cell growth. In this study, we fabricated three different widths of a micro-pattern on polydimethylsiloxane (PDMS; 1, 2, and 4 microm). Surface modification of the PDMS was investigated for its capacity to manage proliferation and differentiation of neural-like cells from umbilical cord blood-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…In vitro by RT-PCR, alizarin red and von Kossa-staining, ALP detection, immunohistochemistry and western blot 8,31,[110][111][112][113] In vitro by safranin-O staining, RT-PCR and immunohistochemistry 8,31 In vitro by immunohistochemistry, RT-PCR, calcium imaging and western blot [114][115][116][117] In vivo in parkinsonian rat model, ischemic rat model [118][119][120][121][122][123] In vitro by immunohistochemistry, RT-PCR, PAS-staining, urea and albumin production, western blot and LDL uptake 31,94,124,125 CD34/AC133-positive (hematopoietic progenitor) cells In vitro by RT-PCR 126 In vivo in NOD/SCID mouse model 95,96 Not defined cells from MNC In vitro by immunohistochemistry, whole-cell patch-clamp, western blot and RT-PCR [127][128][129][130][131] In vivo in spinal cord injury and intra-brain injection in rat and NOD/SCID mouse model 73,76,[80][81][82][83][84][86][87][88][89][90][91][92]<...>…”
Section: Mscmentioning
confidence: 99%
“…In vitro by RT-PCR, alizarin red and von Kossa-staining, ALP detection, immunohistochemistry and western blot 8,31,[110][111][112][113] In vitro by safranin-O staining, RT-PCR and immunohistochemistry 8,31 In vitro by immunohistochemistry, RT-PCR, calcium imaging and western blot [114][115][116][117] In vivo in parkinsonian rat model, ischemic rat model [118][119][120][121][122][123] In vitro by immunohistochemistry, RT-PCR, PAS-staining, urea and albumin production, western blot and LDL uptake 31,94,124,125 CD34/AC133-positive (hematopoietic progenitor) cells In vitro by RT-PCR 126 In vivo in NOD/SCID mouse model 95,96 Not defined cells from MNC In vitro by immunohistochemistry, whole-cell patch-clamp, western blot and RT-PCR [127][128][129][130][131] In vivo in spinal cord injury and intra-brain injection in rat and NOD/SCID mouse model 73,76,[80][81][82][83][84][86][87][88][89][90][91][92]<...>…”
Section: Mscmentioning
confidence: 99%
“…A well-confined culture area constructed by the PDMS was used to culture and differentiate AFMSCs sequentially. By using the PDMS material, its oxygen and CO 2 permeability may provide a suitable culturing and differentiating environment for stem cells (Kim et al 2008). Typically, it is composed of culture areas, micropumps, microgate structures, seeding reservoirs, waste reservoirs and fluid microchannels for connecting these devices.…”
mentioning
confidence: 99%
“…An excellent example is the alignment of cells along microgrooves, a phenomenon known as contact guidance [28,29,30,31]. Microstructures also influence basic cellular processes such as adhesion [32,33,34,35,36,37], migration [38,39,40], proliferation [41,42] and differentiation [43,44]. Recently, there has been significant interest towards utilizing microscale topographies in controlling stem cell behavior.…”
Section: Biomaterials With Micro- and Nanoscale Features For Directinmentioning
confidence: 99%
“…Likewise, mouse mesenchymal stem cells (mMSCs) were shown to exhibit an elongated morphology when cultured on microgrooves [46] (Figure 2B). A number of studies have investigated the effect of microgroove widths on differentiation of MSCs [44,47]. It was shown that the differentiation of MSCs into neural-like cells was less pronounced on the 4 μm wide microgrooves compared to narrower 1 and 2 μm microgrooves.…”
Section: Biomaterials With Micro- and Nanoscale Features For Directinmentioning
confidence: 99%